Development of Flash Card Media for Early Reading Student - Syarifah Adinda Maharani; Zaka Hadikusuma Ramadan (Postgraduate, University of Mataram, 2023)
This research aims to study how first-gradestudents improve their reading skills by using digital picture word cards. This study uses the ADDIE development model and is a development research. The sampling technique in this study used simple random sampling by using the Slovin formula in determining the sample. The one-group posttest technique used in this study the experimental class followed the same experimental methodology. Normality and homogeneity tests were used in qualitative and quantitative data analysis methodology. The results of the analysis showed that with a percentage of 92.73%, the professional assessment of learning media design. With a percentage of 90%, the expert assessment of the learning media content is included in the very correct category. With a proportion of 95%, the linguist's assessment of educational media is included. With excellent criteria, the overall validation level of linguists, design experts, and material experts is 92.58%. This digital flash card media turned out to be feasible to use as a learning tool and can improve students' reading skills. The results showed a significant difference between students' initial reading test scores on the pretest and posttest. This conclusion is reinforced by the results of the Piered Sample Test which shows the variance in students' initial reading using digital picture word card media between pretest and posttest with a significance level of 0.000 <0.05. Therefore, it can be said that the use of digital flash card media can help children in elementary schools acquire basic reading skills.